Distributional Effects of Investments in Road Infrastructure : The Case of Colombia's 4th Generation Concession Program - Rodríguez-Castelán, Carlos; Malásquez, Eduardo A.; Franco, Jorge (World Bank, Washington, DC, 2018)
Estimating ex-ante distributional impacts of road infrastructure is increasingly important to better understand the poverty effects of these investments. This note presents such analysis for the ongoing 4th generation (4G) road concessions program in Colombia, which involves the concession of 40 new roads and the transformation of 8,170 kilometers of road network. An ex-ante evaluation of the program suggests that 180,000 jobs will be created and that moderate and extreme poverty would decline by 0.5 and 0.3 percentage points, respectively.